1984
DOI: 10.1007/bf01314299
|View full text |Cite
|
Sign up to set email alerts
|

Significance of lysosomes in the morphogenesis of coronaviruses

Abstract: Virus-containing electron-dense membrane-bound cytoplasmic bodies are described in tracheal epithelial cells of chickens infected with Infectious Bronchitis Virus and in intestinal epithelial cells of swine infected with Porcine Epidemic Diarrhea Virus. Using silver-methenamine staining, phosphotungstic acid staining and acid phosphatase enzyme cytochemical staining of ultra-thin sections, these bodies were shown to be virus-containing secondary lysosomes and residual bodies. The accumulation of viral particle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

1985
1985
2023
2023

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 15 publications
0
18
0
Order By: Relevance
“…Since the 1960's, intact coronaviruses have been reported in lysosomes at late stages of infection (Ducatelle and Hoorens 1984) but the significance of these observations remained unknown in terms of viral dynamics. Here we demonstrated that coronaviruses egress from infected cells by tracking a singular path through lysosomes and then to the surface.…”
Section: Discussionmentioning
confidence: 99%
“…Since the 1960's, intact coronaviruses have been reported in lysosomes at late stages of infection (Ducatelle and Hoorens 1984) but the significance of these observations remained unknown in terms of viral dynamics. Here we demonstrated that coronaviruses egress from infected cells by tracking a singular path through lysosomes and then to the surface.…”
Section: Discussionmentioning
confidence: 99%
“…The first report showing the relevance of endosome-lysosome in CoVs was from a morphological study in which two CoVs (IBV and Porcine Epidemic Diarrhea Virus (PEDV)) were found to accumulate in the lysosomes of cells after infection [36], indicating that the possible functional implication of lysosome in CoVs infection. Subsequent studies have firmly established that the endocytic pathway is the key mechanisms controlling the entry of CoVs into the host cells, and thus the endocytic pathway has been widely investigated as the target of anti-viral therapies, as summarized in Table 2.…”
Section: Involvement Of the Endocytic Pathway In Covs Infectionmentioning
confidence: 99%
“…The role of lysosomes and related acidic compartments in the replication of coronaviruses is not well understood. Coronavirus infection frequently involves the intracellular accumulation of virus-filled, electron-dense structures which have been interpreted to be lysosomes (David-Ferreira andManaker, 1965, Ducatelle andHoorens, 1984). Such structures are observed within 2-3 hr postinoculation and have, therefore, been suggested to be involved in virus uptake (David-Ferreira and Manaker, 1965).…”
Section: Ammoniummentioning
confidence: 99%